One more and one less: a new species of large bromelicolous lizard (Gymnophthalmidae: Anadia) from the Andean cloud forests of northwestern Colombia and the phylogenetic status of Anadia antioquensis - Amézquita, Adolfo; Daza, Juan Manuel; Contreras, Leidy Alejandra Barragán; Orejuela, Catalina; Barrientos, Lucas Santiago; Mazariegos H., Luis A. (Zootaxa, 2022)
The genus Anadia (family Gymnophthalmidae) consists of 19 species. It has remained almost taxonomically stable for decades, scarcely observed, in addition to being one of the less sampled gymnophthalmid genera with respect to molecular phylogenies. New Anadia species are discovered at a relatively low pace, and few specimens are found in the field, probably due to the arboreal habits of many low and mid elevation species. We describe here a new species of Anadia from the cloud forests of northwestern Colombia: the new species is easily diagnosed by the combination of shape and imbrication of dorsal scales, very large body size, the largest within its group, and large and non-overlapping number of longitudinal scale rows around midbody. We also tested the phylogenetic position of the recently described and geographically close A. antioquensis. A phylogenetic analysis based on four genomic regions recovered the new species as sister to A. buenaventura, whereas A. antioquensis was reassigned to the genus Riama. The new species is currently known from only three specimens, collected throughout eight years within less than 5 ha of the Mesenia-Paramillo Nature Reserve. Although its apparent rarity may be due to secretive habits, the species is provisionally declared vulnerable, while new information is available. To stimulate further research on this genus, we also compiled and present here the comparable information on the distribution and morphology of Anadia species. Altogether, the results stress the urge for a new review of the genus with the help of molecular data.